Local Adaptation and Climate Change Vulnerability of the Relict Tree Species Taiwania cryptomerioides Provide Insights Into Its Conservation and Restoration - Yang Lu; Hao Dong; Saibin Fan; Lu Yuan; Yuhui Wang; Zhuang Zhao; Yong Lai; Shixin Zhu; Jinyong Huang; Caipeng Yue; Yongpeng Ma; Ningning Zhang (Evolutionary Applications)
ABSTRACT Rapid climate change is affecting biodiversity and threatening locally adapted species. Relict species are often confined to relatively narrow, discontinuous geographic ranges and provide excellent opportunities to study local adaptation and extinction. Understanding the adaptive genetic variation and genetic vulnerability of relict species under climate change is essential for their conservation and management efforts. Here, we applied a landscape genomics approach to investigate the population genetic structure and predict adaptive capacity to climatic change for Taiwania cryptomerioides Hayata, a vulnerable Tertiary relict tree species in China. We used restriction site‐associated DNA sequencing on 122 individuals across 10 sampling sites. We found three genetic groups across the Chinese range of T. cryptomerioides: the southwest, central‐eastern, and Taiwanese groups. We detected significant signals of isolation by environment and isolation by distance, with environment playing a more important role than geography in shaping spatial genetic variation in T. cryptomerioides. Moreover, some outliers were related to defense and stress responses, which could reflect the genomic basis of adaptation. Gradient forest (GF) analysis revealed that precipitation‐related variables were important in driving adaptive variation in T. cryptomerioides. Ecological niche modeling and GF analysis revealed that the central‐eastern populations were more vulnerable to future climate change than other populations, with range contractions and high genetic offsets, suggesting these populations may be at higher risk of decline or local extinction. These findings deepen our understanding of local adaptation and vulnerability to climate change in relict tree species and will guide conservation and restoration programs for T. cryptomerioides in the future.